(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
The essay provides a critical analysis of a particular use of aIAT test in courtroom. Despite some severe criticism, the aIAT test has already been used in different trials to detect genuine memories. Recently it has been suggested that the aIAT test could be a reliable tool in order to establish what the Italian criminal law defines the psychological element of crime. This essay aims to show that this possible use of the test implies a radical transformation of the juridical categories at stake, both from an ontological and an epistemological point of view.